Building web-based services for practical exercises in parallel and distributed computing - Sukhoroslov, Oleg (Journal of parallel and distributed computing, 2018)
The paper presents an approach to the design and implementation of web-based environments for practical exercises in parallel and distributed computing (PDC). The presented approach introduces minimal development and operational costs by relying on Everest, a general-purpose platform for building computational web services. The flexibility of proposed service-oriented architecture enables the development of different types of services targeting various use cases and PDC topics. The generic execution services support the execution of different types of parallel and distributed programs on corresponding computing systems, while the assignment evaluation services implement the execution and evaluation of solutions to programming assignments. As was demonstrated by teaching two introductory PDC courses, the presented approach helps to enhance students’ practical experience while avoiding low-level interfaces, reducing the grading time and providing a level of automation necessary for scaling the course to a large number of students. In contrast to other efforts, the exploited Platform as a Service model provides the ability to quickly reuse this approach by other PDC educators without installation of the Everest platform. •A service-based environment for practical exercises in PDC is introduced.•A flexible implementation with low development and operational costs is presented.•A practical experience and services developed for various PDC topics are described.•The presented approach is evaluated and contrasted with traditional approaches.